2013
DOI: 10.1089/fpd.2012.1293
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Public Health Relevance ofCampylobacterIsolated from Dairy Cattle and European Starlings in Ohio, USA

Abstract: Dairy cattle serve as a potential source for Campylobacter infection in humans. Outbreaks associated with consumption of either Campylobacter contaminated raw milk or contaminated milk after treatment were previously recorded in the United States. Further, starlings have been implicated in the spread of bacterial pathogens among livestock. Here, we determined the prevalence, genotypic, and phenotypic properties of Campylobacter isolated from fecal samples of dairy cattle and starlings found on the same establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 55 publications
2
35
0
Order By: Relevance
“…Surprisingly, Campylobacter species are abundant in the large intestine, especially in the cecum. Although this genus is usually known to comprise pathogenic bacteria, some species isolated from cattle and starlings show a high resistance to multiple antimicrobial drugs, including ciprofloxacin , gentamicin , and erythromycin (Sanad et al 2013). Finally, Fibrobacter , Dialister , and Succiniclasticum were found more abundant in the stomach than in the small and large intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, Campylobacter species are abundant in the large intestine, especially in the cecum. Although this genus is usually known to comprise pathogenic bacteria, some species isolated from cattle and starlings show a high resistance to multiple antimicrobial drugs, including ciprofloxacin , gentamicin , and erythromycin (Sanad et al 2013). Finally, Fibrobacter , Dialister , and Succiniclasticum were found more abundant in the stomach than in the small and large intestine.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 98 isolates (23 C. jejuni and 75 C. coli) representing different ages, farms, and flaA clusters were tested for antimicrobial susceptibility using Sensititre Campy plates (TREK Diagnostic Systems Inc., USA) as previously described (Sanad et al, 2011(Sanad et al, , 2013. Minimum inhibitory concentrations (MICs) were determined based on Clinical and Laboratory Standards Institute (CLSI, 2012) breakpoint interpretative criteria for Campylobacteraceae.…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…For example, studies have revealed a range of Campylobacter prevalence (up to 70%) in cattle. 31,[74][75][76] Furthermore, although the prevalence of Campylobacter in cattle carcasses and milk samples can be relatively low in comparison to other sources, studies have shown that approximately 15% of beef carcasses/meat can be contaminated with these pathogens. 38,92 In addition, a Campylobacter prevalence of 41.7%, 10.2%, and 4.6% had been previously reported in raw bulk tank milk in Northern Italy, Pakistan, and Poland, respectively, while 6.25% of raw cow milk samples from retail stores were contaminated with Campylobacter in Iran.…”
mentioning
confidence: 99%